2011
DOI: 10.1016/j.ypmed.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Decaying behavioral effects in a randomized, multi-year fruit and vegetable intake intervention

Abstract: Objective To examine the effects of a multi-component, theory-based, 2.5-year intervention on children’s fruit and vegetable (F&V) consumption, preferences, knowledge and body mass index (BMI). Methods Four inner city elementary schools in the Northeastern United States were randomized to an intervention (n = 149) or control group (n = 148) in 2005. F&V consumption during school lunch (measured by plate waste), preferences, and knowledge, as well as BMI were assessed five times across 3.5 years (pre-interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 26 publications
0
90
0
1
Order By: Relevance
“…Middle-to long-term increases are mostly reported in portions per day, ranging from about 0?09 and 0?07 more portions in fruit and vegetables, respectively (74) , to 0?28 portions of fruit and vegetables (75) , or 10 % daily increases in consumption of fruit (76) . The 0?23 and 0?15 portion increases in our preschool study thus are comparable with previous evidence on intervention effects in older children.…”
Section: Discussionmentioning
confidence: 99%
“…Middle-to long-term increases are mostly reported in portions per day, ranging from about 0?09 and 0?07 more portions in fruit and vegetables, respectively (74) , to 0?28 portions of fruit and vegetables (75) , or 10 % daily increases in consumption of fruit (76) . The 0?23 and 0?15 portion increases in our preschool study thus are comparable with previous evidence on intervention effects in older children.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were of varying study designs, with 42 48,50,53,54,[57][58][59]62,63,[67][68][69]71,[73][74][75][76][77][78][79][80][81]83,84,86,87,89,90,[93][94][95][96][97]98,102,103,[106][107][108][109][110][111][112][113][114][115][116][117][118][119]124 experimental (largely cluster trials) and 34 [40][41][42][43][44][45][46][47]49,51,…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
“…studies seldom reported means and standard deviations), it was possible to conduct meta-analysis for only a small subset of interventions in this category (n = 13 targeted interventions). The fifty-two studies are therefore synthesised narratively in terms of whether they followed a universal (n = 16 44,45,57,64,[74][75][76][77]86,88,[96][97][98][100][101][102]104,105 ) or a targeted (n = 36 54,56,[58][59][60][61][62][63][65][66][67][68][69][70][71][72][73][78][79][80][81][82][83][84][85]87,[89][90][91][92][93][94][95]99,103,106 ) approach. The results are also summarised in Table 41 (universal-approach studies) and …”
Section: Targeted Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Lastly, multicomponent interventions may require significant funding and involvement from teachers, cafeteria staff, and parents. 38 Many of the published multicomponent studies were funded by large research organizations such as the National Cancer Institute, 37,[39][40][41][42][43] the National Institute of Health, 44,45 and the Centers for Disease Control and Prevention. 41,44 Therefore, simple cafeteria interventions may be more practical for many schools with limited resources.…”
Section: Discussionmentioning
confidence: 99%